The Fund, Commercial Banks, and Member Countries - Mentre, Paul (Occasional Papers; Occasional Paper ;, 1984)
This paper summarizes recent developments in the relationships between the IMF, member countries, and commercial banks, with specific reference to five European countries. The paper also highlights that Better assessment of trends in the market and of the attitude of commercial banks toward borrowing countries. These would include: a deeper analysis of capital flows, with special attention to interbank transactions; an improvement in the collection of statistical data and additional efforts made by member countries to release adequate information; and a further examination of the usefulness of setting up in the Fund an internal country risk assessment statistical model. The report also suggests that there should be adequate Fund involvement in rescheduling negotiations through discussions with Paris Club members on rescheduling patterns and possibly through an elaboration of guidelines for rescheduling bank claims; appropriate action to cope with liquidity crises; and adequate international cooperation among central banks acting as lenders of last resort.